Impact of Different Toilet Cleaning/Disinfecting Regimens on Reducing the Risk of Exposure to Toilet-Borne Pathogens in American Household Restrooms - Stephanie A. Boone; Nick D. Childress; Norma Patricia Silva-Beltrán; Julie McKinney; M. Khalid Ijaz; Charles P. Gerba (Hygiene)
Restrooms are associated with the transmission of bacterial and viral illnesses. Disinfecting contaminated surfaces is associated with reducing transmission risk. The goal of this study was to determine how cleaning/disinfecting frequency affects restroom pathogen contamination. The Phase 1 intervention included cleaning toilet surfaces (the toilet bowl, water, and rim) using 9.5% w/w hydrochloric acid. The Phase 2 intervention used fomite-specific products to clean/disinfect additional restroom surfaces, including the vanity countertop, sink faucet handle, toilet seat, flush handle, floor, and doorknob. A designated household member was responsible for cleaning/disinfecting surfaces at the beginning of each interval. Fomite sample collection was randomized, and samples were tested for heterotrophic, coliform, and Escherichia coli bacteria after specified intervals: 1, 2, 3, or 7 days. The greatest numbers of bacteria and largest reductions occurred on fomites after three days. A statistically significant difference was found for heterotrophic bacteria (p = 0.009), coliforms (p = 0.10), and E. coli (p = 0.13) with cleaning/disinfecting every three days. A quantitative microbial risk assessment (QMRA) estimated a >98% reduction in risk of infection by norovirus with an every-3-day cleaning/disinfection routine on the most heavily contaminated sites. Results indicate an optimal cleaning frequency of twice weekly for minimizing exposure to pathogens.